Implementation of Flipped Learning Classroom in Academic Context of Higher Education - Baybabaeva Shoiraxon Ismatovna (International Journal on Integrated Education, 2022)
The article deals with the issues based on implementation of flipped learning classroom in academic context of higher education. The “Flipped” learning approach is becoming increasingly popular not only in schools, but also in universities. It creates opportunities for solving complex pedagogical problems in education. Since, on the one hand, the teacher can work individually with students with different levels of education, who are representatives of different cultures. So, on the other hand, it allows the teacher to organize the joint work of students on projects in the classroom by groups artificially created by him, from students of different cultures and levels of education.